The analysis of the effect of monetary policy on consumption and investment in Thailand - Jirawan Suwannajak (2018)
© Springer International Publishing AG 2018. This study highlights on the analysis of Thai monetary policy transmission channels, i.e. interest rate, credit, exchange rate, and asset price channels, to private consumption and private investment. The analytical methods are Time Varying Parameter Vector Autoregressive (TVP-VAR) with stochastic volatility, and its impulse response function. The results showed that the credit channel contribute the greatest impact on private consumption and investment. We also found that the effect of monetary policy to private consumption and investment are vary over time.